Aleksander Walicki’s Upominek zecerom od korektora as an Example of 19th-Century Orthoepic Guidance - Sokólska, Urszula; Strawińska, Anetta Bogusława (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2024)
The aim of the article is, first of all, to present a synthetic study of a little-known 19thcentury guide for printers by Aleksander Walicki entitled Upominek zecerom od korektora published in 1886 in Kraków. Secondly, placing the orthographic issues referred to in the book in a broad purist perspective, against the background of the 19th-century norm in the eastern borderland variant. Thirdly, drawing attention to the provenance of the words indicated in the guide for printers, which largely reveal the regional identity of its author. As a language enthusiast, and above all an extreme purist, Walicki downplays the fact that perfect knowledge of the linguistic system and usage is necessary to formulate normative recommendations. Sometimes ignorance of these factors leads him to make to erroneous normative judgements.